Copy Number Analyses Identified a Novel Gene: APOBEC3A Related to Lipid Metabolism in the Pathogenesis of Preeclampsia - Liu, Nan; Guo, Yu-Na; Wang, Xiao-Jin; Ma, Jue; He, Yun-Ting; Zhang, Fang; He, Hao; Xie, Jin-Liang; Zhuang, Xu; Liu, Meng; Sun, Jian-Hua; Chen, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Preeclampsia is a heterogeneous and complex disease with its pathogenesis mechanism not fully elucidated. A certain subset of patients with preeclampsia exhibit disturbances in lipid metabolism before clinical symptoms. Moreover, there is a tendency for preeclampsia to run in families. Whether genetic factors play a role in abnormal lipid metabolism during the incidence of preeclampsia has not been well investigated. Methods Preeclampsia patients (n=110) and healthy age- and gravidity-matched pregnant women (n=110) were enrolled in this study. Peripheral blood specimens were used for genomic analysis (n=10/group) or laboratory validation (n=100/group). We retrospectively obtained the baseline clinical characteristics of 68 preeclampsia patients and 107 controls in early pregnancy (12 to 14 gestational weeks). Correlation analyses between differential genes and baseline lipid profiles were performed to identify candidate genes. In vitro and in vivo gain-of-function models were constructed with lentivirus and adeno-associated virus systems, respectively, to investigate the role of candidate genes in regulating lipid metabolism and the development of preeclampsia. Results We observed that preeclampsia patients exhibited significantly elevated plasma TC (P=0.037) and TG (P<0.001) levels and increased body mass index (P=0.006) before the disease onset. Within the region of 27 differential copy number variations, six genes potentially connected with lipid metabolism were identified. The aberrant copies of APOBEC3A, APOBEC3A_B, BTNL3, and LMF1 between preeclampsia patients and controls were verified by quantitative polymerase chain reaction. Especially, APOBEC3A showed a significant positive correlation with TC (P<0.001) and LDL (P=0.048) in early pregnancy. Then, our in vitro data revealed that overexpression of APOBEC3A disrupted lipid metabolism in HepG2 cells and affected both cholesterol and fatty acid metabolisms. Finally, in vivo study in a hepatic-specific overexpressed APOBEC3A mouse model revealed abnormal parameters related to lipid metabolism. Pregnant mice of the same model at the end of pregnancy showed changes related to preeclampsia-like symptoms, such as increases in sFlt-1 levels and sFlt-1/PLGF ratios in the placenta and decreases in fetal weight. Conclusion Our findings established a new link between genetics and lipid metabolism in the pathogenesis of preeclampsia and could contribute to a better understanding of the molecular mechanisms of preeclampsia.